2022
DOI: 10.33394/j-ps.v10i3.5696
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Self Organized Learning Environments (SOLE) Approach on Student's Learning Motivation and Achievement in History Lessons

Abstract: Crisis education going on Indonesian people now this cause worries, especially for parents and party schools that have trusted as institution education. When Indonesia was hit by the covid pandemic – 19 in the middle March 2020, students study from distance far away (PJJ), and this PJJ the more add crisis education in Indonesia. Study this aim for knowing influence motivation and performance study student to approach learning self organized learning environments (SOLE) at eye lesson history in class X SMAN 1 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…These competencies can be linked to the Technological Pedagogical Content Knowledge (TPACK) framework. Integrating TPACK with different learning models, such as the Self-Organized Learning Environment (SOLE) model and the Student Teams Achievement Division (STAD) cooperative model, can be highly beneficial (Nasution et al, 2018;Kusasi, 2021;Marlina, 2021;Abyan et al, 2022;Satriani et al, 2022). The STAD cooperative learning model has been shown to have a positive impact on improving students' physics learning outcomes (Lovisia, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These competencies can be linked to the Technological Pedagogical Content Knowledge (TPACK) framework. Integrating TPACK with different learning models, such as the Self-Organized Learning Environment (SOLE) model and the Student Teams Achievement Division (STAD) cooperative model, can be highly beneficial (Nasution et al, 2018;Kusasi, 2021;Marlina, 2021;Abyan et al, 2022;Satriani et al, 2022). The STAD cooperative learning model has been shown to have a positive impact on improving students' physics learning outcomes (Lovisia, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The STAD cooperative learning model has been shown to have a positive impact on improving students' physics learning outcomes (Lovisia, 2019). A study by Satriani et al (2022), investigating the effects of the SOLE learning model on student achievement in physics, has revealed that the implementation of this model had a positive influence on learning outcomes. This is because SOLE promotes students' learning independence, aligning with the indicators of independent learning (Firdaus et al, 2021).…”
Section: Introductionmentioning
confidence: 99%